Why Adolescents Participate in a Music Contest and Why They Practice – The Influence of Incentives, Flow, and Volition on Practice Time - Bullerjahn, Claudia; Dziewas, Johanne; Hilsdorf, Max; Kassl, Christina; Menze, Jonas; Gembris, Heiner (Frontiers in Psychology, 2020)
Music contests are a means of discovering talents and promoting musical abilities. Participation in a contest is usually preceded by many years of practice requiring a high level of motivation and a supportive environment, especially regarding family. Despite the importance participation in music contests may have for musical development, there is a considerable research deficit. The annual music contest “Jugend musiziert” (youth making music) is the most important musical competition for highly gifted young musicians in Germany. There has been comprehensive research on the participants of “Jugend musiziert” by Hans Günther Bastian in the 1980s and 1990s, but since then, only very little research has been published. In 2017, we started a large-scale study on the participants at the national level, covering a broad range of topics, including sociocultural background, development and learning, performance practice, personality traits, motivation, and musical performance anxiety. A standardized paper-pencil questionnaire was administered to approx. 2,260 participants and a total of 1,143 valid questionnaires were returned (age 9 to 24; M = 15; SD = 2.1, female = 62%). Using principal component, variance, correlation, and linear discriminant analyses, interdependencies between practice time and motivational factors were analyzed in this paper. Concerning practice time, major differences between participants of different contest categories became clear, with classical musicians practicing the most. Practice time, as well as parental support and supervision, correlated with age: Older participants spent, on average, more hours practicing and received less support and supervision. Challenge was the most important incentive for all participants, but more decisive for participants in the classical solo contest than in the ensemble category. Female participants were more prone to fear incentives than males. Participants who practiced a lot scored higher on general flow than the participants with a smaller amount of practice and also showed significantly more perseverance. Moreover, participants of the pop solo contest experienced more general flow than all other participants; ensemble players showed more social focus than participants in the classical solo contest. All in all, participants of different contest categories could be discerned by practice time and prototypical motivational aspects.